To Cage the Red Dragon : SEATO and the Defence of Southeast Asia 1955-1965 - Fenton, Damien (NUS Press, 2012)
The South East Asia Treaty Organization (SEATO) was the focal point of Western military efforts to deter, and if need be defeat, communist aggression in Southeast Asia between 1955 and 1965. In this mission it was, on its own terms entirely successful; and none of the SEATO regional members (Pakistan, Thailand or the Philippines) succumbed to communist rule, then or later. Most Southeast Asian countries emerged from the geo-strategic vulnerabilities of the immediate post-colonial period un-swayed by the efforts of local (or foreign-based) communist movements. To Cage the Red Dragon examines the role of SEATO during its first ten years as a military alliance in helping secure this outcome. The book also details actions by member states (notably France and Pakistan) that led the United States, SEATO's primary advocate, to sideline the alliance in 1965, a step that precipitated its subsequent rapid decline.